Effect of Essential Oils from Ginger (Zingiber officinale) and Turmeric (Curcuma longa) Rhizomes on Some Inflammatory Biomarkers in Cadmium Induced Neurotoxicity in Rats - Ayodele Jacob Akinyemi; Philip Adeyemi Adeniyi (Journal of Toxicology)
Studies have revealed that anti-inflammatory agents could provide beneficial effect in lowering the incidence/progression of neurological diseases. Hence, this study sought to investigate the effect of essential oils from Nigeria ginger and turmeric rhizomes on some cytokines in cadmium induced neurotoxicity. The result revealed that essential oil from ginger and turmeric rhizomes exerts anti-inflammatory effect by preventing alterations of some cytokines/inflammatory biomarkers (IL-6, IL-10 and TNF-Alpha) levels and inhibits both hippocampus and prefrontal cortex acetylcholinesterase (AChE) and adenosine deaminase (ADA) activities (important enzymes relevant in the management/prevention of neurodegenerative diseases) in Cd treated rats. In conclusion, essential oil from ginger and turmeric rhizomes exerts anti-inflammatory properties in Cd induced neurotoxicity. The observed effect could be due to the volatile compounds as revealed by GC-MS analysis.